Publish, Don’t Perish: Research and Publication for Otolaryngologists - José Florencio F. Lapeña (Philippine Journal of Otolaryngology Head and Neck Surgery, 2014)
“Research, no matter how ‘good’, is incomplete, until it has been published.”1